Adult perceptions of the relative harm of tobacco products and subsequent tobacco product use: Longitudinal findings from waves 1 and 2 of the population assessment of tobacco and health (PATH) study. (July 2020) - Elton-Marshall, Tara; Driezen, Pete; Fong, Geoffrey T.; Cummings, K. Michael; Persoskie, Alexander; Wackowski, Olivia; Choi, Kelvin; Kaufman, Annette; Strong, David; Gravely, Shannon; Taylor, Kristie; Kwan, Jonathan; et al.
Highlights: Perceptions of harm of tobacco products are important in predicting product use. Harm perceptions predict product uptake in non-users and continued use among users. Tobacco control strategies may benefit from understanding/addressing perceptions. Abstract: Objectives: To examine: (1) How perceptions of harm for seven non-cigarette tobacco products predict subsequent use; (2) How change in use is associated with changes in perceptions of product harm; (3) Whether sociodemographic variables moderate the association between perceptions and use. Methods: Data are from the adult sample (18+) of the Population Assessment of Tobacco and Health (PATH) Study, a nationally representative longitudinal cohort survey conducted September 2013-December 2014 (Wave 1 (W1) n = 32, 320) and October 2014-October 2015 (Wave 2 (W2) n = 28, 362). Results: Wave 1 users and non-users of e-cigarettes, filtered cigars, cigarillos, and pipes, who perceived these products as less harmful had greater odds of using the product at W2. For the other products, there was an interaction between W1 perceived harm and W1 use status in predicting W2 product use. At W2, a smaller percentage of U.S. adults rated e-cigarettes as less harmful than cigarettes compared to W1 (41.2% W1, 29.0% W2). Believing non-cigarette products to be less harmful than cigarettes was more strongly associated with subsequent product use in the oldest age group (55+ years) while weaker effects were observed in the youngest age group (18–24 years). This moderating effect of age was significant for e-cigarettes, hookah, traditional cigars, and cigarillos. Conclusions: Strategies to prevent initiation and promote cessation of these products may benefit from understanding and addressing perceptions of these products.